The use of the 25 Sprotte needle markedly reduces post-dural puncture headache in routine neurological practice. (February 2016) - Bertolotto, Antonio; Malentacchi, Maria; Capobianco, Marco; di Sapio, Alessia; Malucchi, Simona; Motuzova, Yana; Pulizzi, Annalisa; Berchialla, Paola; Sperli, Francesca
Objectives: The objectives of this article are to test the feasibility of lumbar puncture (LP) using 25-gauge (G) needles in daily neurological practice and to compare the risk of post-dural puncture headache (PDPH) with four types of needles. Methods: In a prospective rater-blind study, pros and cons of four different LP needles, the 20G Quincke (20Q), 22G Sprotte (22S), 25G Whitacre (25W) and 25G Sprotte (25S), were evaluated in 394 LPs performed by seven neurologists. The neurologist performing the LP recorded the type and size of needle, intensity of pain, safety, time of the procedure and failure or success. Between five and 15 days later another neurologist, blind to the type of needle used, completed an ad-hoc questionnaire for PDPH. Results: PDPH developed in 35.9% patients when using a 20Q needle, and in 12.9%, 6.8% and 1.6%, respectively, when using a 22S, 25W or 25S needle. The difference in incidence of PDPH following LP performed with the 20Q needle and the 25S or 22S was statistically significant ( p < 0.001 and p = 0.008, respectively) and it approached significance when comparing the 25S and 25W ( p = 0.06). As 25W and 25S needles need CSF aspiration, LP requires more time and skill. Pain caused by LP was similar with the four needles. Conclusion: The use of the 25S needle in diagnostic LP reduces the frequency and severity of PDPH.